A Heuristic Video Recommendation Algorithm based on Similarity Computation for Multiple Features Analysis - Li, Shuangyuan (Recent Advances in Computer Science and Communications, 2022)
Objective: The short video applications have achieved great success in recent years. The number of videos being shot and uploaded to these platforms has significantly increased. In this way, mining and recommending videos for users based on their interests has become a challenging problem in these video distribution platforms. Under this case, it becomes particularly important to design efficient video recommendation algorithms for these platforms. In order to solve the problem faced by high sparsity and large scale data sets in the field of media big data mining and recommendation, a heuristic video recommendation algorithm for multidimensional feature analysis and filtering is proposed. Methods: Firstly, the video features are extracted from multiple dimensions, such as user behavior and video tags. Then, the similarity analysis is carried out. The video similarity degree is calculated by weighting to obtain the similar video candidate set and filter the similar video candidate set. After that, the videos with the highest scores are recommended to users by sorting. Finally, the video recommendation algorithm proposed in this paper is implemented by using the C language. Results: Compared with the benchmark, the proposed video recommendation algorithm has improved the accuracy by 6.1%-136.4%, the recall rate by 19.3%-30.9%, the coverage rate by 55.6%-59.5%, the running time by 42.7%-60.4%, and the cache hit ratio by 10.9%-47.4%. Conclusion: The proposed algorithm can effectively improve the accuracy, recall rate, coverage rate, running time, and cache hit ratio.
Keywords: cache hit ratio